PRELIMINARY EXPERIMENTS ON MONOCULTURE OF CHANOS CHANOS (FORSKAL) AND ITS POLYCULTURE WITH PENAEUS MONODON FABRICIUS - Nammalwar, P; Kathirvel, M (Indian Journal of Fisheries, 2011)
Preliminary experiments on monoculture of milk fish, Chanos chanos and its polyculture with tigerprawn, Penaeus monodon were carried out in the grow-out pond system at Mariculture farm, Muttukadunear Madras. During the six-month rearing, C. chanos attained an average size of 234.6 mm (76.9 g) inthe monoculture trial and 159.8 to 231.8 mm (39.0 to 90.9 g) in the polyculture experiments. In the caseof tiger prawn, the growth was poor and the sizes recorded at harvest were 119.4 to 135.1 mm (12.8 to 17.8 g).The rate of recovery ranged from 8.4 to 87.0% for fish and 20.6 to 35.3 % for prawn. The reasons forpoor growth and survival of fish and prawn in relation to environmental and other factors are discussed.